2016
DOI: 10.1007/s00428-016-1979-9
|View full text |Cite
|
Sign up to set email alerts
|

An international study comparing conventional versus mRNA level testing (TargetPrint) for ER, PR, and HER2 status of breast cancer

Abstract: To compare results from messenger RNA (mRNA)-based TargetPrint testing with those from immunohistochemistry (IHC) and in situ hybridization (ISH) conducted according to local standard procedures at hospitals worldwide. Tumor samples were prospectively obtained from 806 patients at 22 hospitals. The mRNA level of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) was assessed by TargetPrint quantitative gene expression readouts. IHC/ISH assessments were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Our results showed a high concordance between TargetPrint and IHC/FISH for ER (97.5%) and HER2 (97.5%), and moderate concordance for PgR (77.5%). These results are similar to those reported previously, with concordances of approximately 96% for ER and 95% for HER2 [ 13 , 20 ]. Regarding PgR, the concordance for mRNA and IHC analysis has been shown to be approximately 80% in previous studies [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed a high concordance between TargetPrint and IHC/FISH for ER (97.5%) and HER2 (97.5%), and moderate concordance for PgR (77.5%). These results are similar to those reported previously, with concordances of approximately 96% for ER and 95% for HER2 [ 13 , 20 ]. Regarding PgR, the concordance for mRNA and IHC analysis has been shown to be approximately 80% in previous studies [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…The correlation between the Ki67 and EP and EPclin scores was examined using the Pearson correlation coefficient. Agreement measurements between binary (positive versus negative) TargetPrint mRNA and IHC classifications were based on two-way contingency table analysis and included overall correlation and positive agreement (defined as the number of samples classified positive by both IHC and mRNA divided by the number of positive samples using IHC) [ 13 ]. Statistical analysis was performed with the SPSS statistics 19 software (IBM, Armonk, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In one study assessing mRNA levels by TargetPrint, most breast carcinomas (five of eight cases) with 1-10% ER expression by IHC were negative by RNA analysis. 25 In this study however, there were even more cases (n = 15) with negative IHC ER results that were ER positive by RNA analysis. Similarly, an additional study found a subset of cases interpreted as ER negative by IHC but positive by RNA expression using the GeneChip Human Genome U133 Plus 2.0 array.…”
Section: Discussionmentioning
confidence: 51%
“…In general, good concordance has been reported between the ER status determined by IHC and the ER status ascertained using MapQuant, 39 TargetPrint, 40 and 3 molecular assays, BluePrint, MammaPrint, and TargetPrint. 41 Allott et al 42 also found high concordance for ER status of >10% positivity between IHC and RNA-based intrinsic subtypes.…”
Section: Introductionmentioning
confidence: 88%